2017
DOI: 10.3389/fncel.2017.00161
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effects of Chronic Folate Deficiency in the Ts65Dn Mouse Model of Down Syndrome

Abstract: Folate is an important B vitamin naturally found in the human diet and plays a critical role in methylation of nucleic acids. Indeed, abnormalities in this major epigenetic mechanism play a pivotal role in the pathogenesis of cognitive deficit and intellectual disability in humans. The most common cause of cognitive dysfunction in children is Down syndrome (DS). Since folate deficiency is very common among the pediatric population, we questioned whether chronic folate deficiency (CFD) exacerbates cognitive dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…Mice require less than 10 min to build a nest ( 39 ), and standard experimental protocol allows nest building for the duration of the 12 h dark period. Similar to a previous study’s findings, the folic acid deficient mice in both weeks 2 and 6.5 were significantly less capable of building a nest than the mice fed adequate folic acid and protein, p < 0.05 ( 12 ). Mice performed nest building activity during week 2 as they were acclimating to the experimental diets and at week 6.5, toward the end of the study.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Mice require less than 10 min to build a nest ( 39 ), and standard experimental protocol allows nest building for the duration of the 12 h dark period. Similar to a previous study’s findings, the folic acid deficient mice in both weeks 2 and 6.5 were significantly less capable of building a nest than the mice fed adequate folic acid and protein, p < 0.05 ( 12 ). Mice performed nest building activity during week 2 as they were acclimating to the experimental diets and at week 6.5, toward the end of the study.…”
Section: Resultssupporting
confidence: 87%
“…Despite contrary studies, there exists a narrow advantage of supplementation with folic acid for loss of learning memory in dementia ( 11 ). One study in Ts65Dn mice fed folic acid deficient diets documented shortened dendritic lengths in the dentate gyrus, cells that play a significant role in attention and contextual learning ( 12 ). In addition to protein and folate, a moderate, chronic intensity of exercise is necessary for an optimal inflammatory response as an efficient strategy for prevention of chronic disease ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…This observed folate deficiency in patients with DS is particularly intriguing when taking into account reported gene-environment risk factors in certain populations that support the notion that peri-conceptional nutritional supplementation may reduce the risk of having a child with DS in mothers carrying polymorphisms in certain folate pathway genes 30 . These findings of folate depletion in children with DS also highlight recent work describing the impact of folate depletion on brain structure and function in a mouse model of DS with the possible implication that folate insufficiency promotes the progression of structural and functional abnormalities in DS 31 . However, further research is needed to investigate the role of folate insufficiency in cognitive dysfunction in DS and the potential role for folate status monitoring and supplementation as an approach to prevent cognitive decline.…”
Section: Discussionsupporting
confidence: 70%
“…Other researchers reported that the vitamin deficiency exacerbated the cognitive impairment [ 11 , 13 ]. A recent study showed that folate deficiency impaired cognition and attention during the nesting test in Ts65Dn mice [ 14 ]. However, these studies cannot determine the role of folate in cognitive function due to other B vitamins that were also deficient in the diet.…”
Section: Introductionmentioning
confidence: 99%